Nanocatalizadores para procesos medioambientales: obtención de energía y eliminación de contaminantes - Barroso-Martín, Isabel (UMA Editorial, 2022)
In the present doctoral thesis, two main concerns modern society is experiencing have been addressed: on the one hand, the need of developing clean, renewable energy sources that help to reduce the heavy reliance on fossil fuels and, on the other hand, the urgency to unfold greener processes to palliate water pollution. Regarding the first covered issue, several catalysts families based on transition and noble metals have been synthesized, fully characterized and tested in hydrodeoxygenation (HDO) reaction. In order to fully understand the catalytic behaviour of the prepared catalysts, crystalline nature, textural properties, morphology, acidic nature and surface chemical composition of all catalysts (and precursors, when required) were characterized by X-ray powder diffraction (XRD), N2 adsorption-desorption isotherms, transmission electron microscopy (TEM), ammonia thermoprogrammed desorption (NH3-TPD) and X-ray photoelectron spectroscopy (XPS). Oher characterization techniques have been performed for some but not all catalysts, such as hydrogen thermoprogrammed reduction (H2-TPR), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), X-ray fluorescence (XRF) and scanning electron microscopy (SEM).
With respect to the second discussed topic, two sets of photoactive catalysts based on gold and reducible oxide CeO2 as dopants for titania-based nanostructures have been studied in photocatalytic processes carried out at ambient conditions. Both photocatalysts families were characterized by XRD, N2 adsorption-desorption isotherms, TEM, XPS and diffuse reflectance UV-visible spectroscopy (DRUV-vis) in order to assess the crystalline phases present, textural properties, morphology and metallic dispersion, surface chemical composition and optical properties, respectively. Additionally, RMN-ss was performed for AuCu supported on Ti-SBA catalysts and Raman spectroscopy and time-resolved photoluminescence (TRPL) for ceria-titania nanostructures.
Keywords: Catalizadores - Tesis doctorales; Cinética química - Tesis doctorales; Catalisis; Estructura y Reactividad de Catalizadores Solidos; Ingenieria y Tecnologia del Medio Ambiente; Cinetica Quimica